2019
DOI: 10.1002/ceat.201900142
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Phase Reforming in a Microreactor: The Role of Surface Bubbles

Abstract: In heterogeneous catalysis, the creation of gaseous products as bubbles in a liquid phase on the catalytic surface is associated with slip phenomena. In a microreactor, the slip length at the gas‐liquid interface is in the same order of magnitude as the reactor dimensions, which can affect fluid dynamics and transport phenomena. Here, the interplay of momentum, heat and mass transfer in a microreactor, when bubbles form on the catalytic surface, was investigated using two‐dimensional simulations. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Theoretical work of Datsevich (2003a;2003b;2004;2005, Oehmichen et al, 2010 has shown that formation of gas bubbles can influence transfer inside particles dramatically, whereas we have recently demonstrated in a microfluidic device, mimicking pores in a catalyst support, that both retardation as well as enhancement of transport on the pore is possible (Espinosa et al, 2018). Very recently, a simulation using APR of glycerol as model reaction showed the effect of bubbles on the kinetics and transport phenomena in a 2D system (Ripken et al, 2019). This clearly needs further research to decide if such effects experimentally contribute in practical 3D porous catalysts.…”
Section: Effect Of Mass Transfermentioning
confidence: 95%
“…Theoretical work of Datsevich (2003a;2003b;2004;2005, Oehmichen et al, 2010 has shown that formation of gas bubbles can influence transfer inside particles dramatically, whereas we have recently demonstrated in a microfluidic device, mimicking pores in a catalyst support, that both retardation as well as enhancement of transport on the pore is possible (Espinosa et al, 2018). Very recently, a simulation using APR of glycerol as model reaction showed the effect of bubbles on the kinetics and transport phenomena in a 2D system (Ripken et al, 2019). This clearly needs further research to decide if such effects experimentally contribute in practical 3D porous catalysts.…”
Section: Effect Of Mass Transfermentioning
confidence: 95%
“…23 In previous work, we numerically investigated the influence of bubbles on the momentum, heat and mass transfer for APR of a 10 wt% glycerol aqueous solution, assuming a 2Dconfiguration for a microchannel reactor. 24 In that work, hemispherical or elliptical bubbles with contact angles of up to 90°against the catalytic surface were modeled, resulting in a significant coverage of the catalytic surface. This first study indicated that the conversion and the temperature profile in the microreactor are mainly determined by the fraction of the catalytic surface covered by bubbles, with no effect of the bubble protrusion angle.…”
Section: Introductionmentioning
confidence: 99%